The Relationship Between Psychological Distress, Negative Cognitions, and Expectancies on Problem Drinking: Exploring a Growing Problem Among University Students. (January 2016) - Obasi, Ezemenari M.; Brooks, Jessica J.; Cavanagh, Lucia
Few studies have sought to understand the concurrent relationship between cognitive and affective processes on alcohol use and negative alcohol-related consequences, despite both being identified as predictive risk factors in the college population. More research is needed to understand the relationships between identified factors of problem drinking among this at-risk population. The purpose of this study was to test if the relationship between psychological distress and problem drinking among university students ( N = 284; M –age = 19.77) was mediated by negative affect regulation strategies and positive alcohol-related expectancies. Two latent mediation models of problem drinking were tested using structural equation modeling (SEM). The parsimonious three-path mediated latent model was supported by the data, as evidenced by several model fit indices. Furthermore, the alternate saturated model provided similar fit to the data, but contained several direct relationships that were not statistically significant. The relationship between psychological distress and problem drinking was mediated by an extended contributory chain, including negative affect regulation and positive alcohol-related expectancies. Implications for prevention and treatment, as well as future directions, are discussed.